Upade myā, naññʻ upade myā, ʻlup thum lup naññʻ myā nhaṅʻʻ upade kaiʻ suiʻ ʻā nā taññʻ saññʻ a minʻ myā (Praññʻ sūʻ Lvhatʻ toʻ, 1986)
Acts, rules, and procedures and orders having the force of acts enacted by the Praññʻ sūʹ Lvhatʻ toʻ